Repositioning study of flubendazole for treating lung cancer and meningoencephalitis using an oral lipid nanosystem - Yukuyama, Megumi Nishitani (2023)
Nanoemulsions have wide application, presenting several properties such as the solubilization of poorly soluble drugs in water, promoting the increase of their bioavailability, allowing greater stability of the formulation and, due to its property as a carrier, promoting their modified release. Nanoemulsion development and optimization can be rationally performed using a suitable design of experiment (DoE). Among the processes for obtaining nanoemulsions, D-phase emulsification method (DPE) is considered advantageous because it allows the development of nanoemulsions without requiring the use of specific equipment, strict adjustment of the hydrophilic-lipophilic balance of the system, high temperatures, surfactant concentrations, or solvents. Through the combination of DPE and DoE, nanoemulsions with a mean particle size of less than 100 nm and a high concentration of the oil phase (60.0% w/w) were obtained using oil approved for oral use and which offered greater drug solubility for flubendazole (FLZ). FLZ belongs to class II of the biopharmaceutical classification system, and is a microtubule targeting agent (MTA) and candidate for drug repositioning for several diseases. In vivo trials have been performed for treating cryptococcal meningitis and malignant wounds in lung cancer, and results have shown efficacy of approximately 30% and 100% for the respective treatment. The nontoxicity of this nanoemulsion was demonstrated in a test using an invertebrate model of Galleria mellonella. For the in vitro evaluation of the oral efficacy of this nanoemulsion, a pilot dissolution method specific to the nanoemulsion was developed, through the optimization of the biphasic method combined with the modified cylinder method. Results showed agreement between the results obtained in this dissolution test and the results obtained in vivo, indicating the superiority of the developed nanoemulsion compared to the drug in suspension or control, and possible mechanisms for the respective results were discussed. Additionally, review articles were published describing several mechanisms of action of MTA in lung cancer, and targeting nanostructured systems to the lymphatic system in cancer treatments. Thus, the present work indicates the potential of the nanoemulsion containing FLZ as a new drug or adjuvant drug for treating cryptococcal meningitis and lung cancer.